2008
DOI: 10.1002/bmc.1132
|View full text |Cite
|
Sign up to set email alerts
|

Determination of urinary androgen glucuronides by capillary electrophoresis with electrospray tandem mass spectrometry

Abstract: Capillary electrophoresis-electrospray tandem mass spectrometry (CE-ESI/MS/MS) is a simple and highly sensitive method for quantifying seven urinary androgen glucuronides. The urine samples were diluted and filtered through a membrane filter, and the filtrate was injected into a CE-MS/MS system without further sample preparation steps such as extraction and derivatization. The calibration ranges were 0.01-5 microg/mL for glucuronides of androsterone and 11beta-OHAn-3G, and 5-500 ng/mL for glucuronides of 11-ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A library search strategy based on mass fragmentation patterns using MS/MS is best suited to identifying available molecules for which MS/MS spectra have been collected in databases. Peptides are often neglected in metabolomic analyses, but their repeated amino acid structure and relatively well‐characterized fragmentation patterns, combined with the availability of sequence databases, renders their identification much simpler 3–6. Often, only very limited structural information can be obtained from MS/MS spectra of singly charged small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A library search strategy based on mass fragmentation patterns using MS/MS is best suited to identifying available molecules for which MS/MS spectra have been collected in databases. Peptides are often neglected in metabolomic analyses, but their repeated amino acid structure and relatively well‐characterized fragmentation patterns, combined with the availability of sequence databases, renders their identification much simpler 3–6. Often, only very limited structural information can be obtained from MS/MS spectra of singly charged small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, CE-MS, differently from LC-MS, has proved its tolerance to the use of inorganic buffers. Last but not least, the use of chiral selectors in solution (mainly CDs), although with some adjustments, can also be compatible with CE-MS. With specific regards to the variety of forensic applications herein reviewed, it is worthy to report some examples of improvement of the analytical performances: (i) analysis time can markedly be reduced in CE, as reported by Simó et al, who compared a long-lasting HPLC analysis (40 min) versus a rapid CZE-TOF-MS lasting only 8 min [163]; (ii) sensitivity has proved to be similar, and sometimes higher, when comparing CE-MS to other hyphenated techniques [145,165]; (iii) CE separation, moreover, offers the chance to analyze a greater variety of analyte categories, and particularly charged molecules such as glucuronides of drugs and hormones, which are of the highest forensic toxicological interest [91,118]; (iv) finally, separation buffers that can be used in CE separations are of a greater variety than the ones used in LC-MS, as was reported by several authors [31,32,50,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al reported a CZE-ESIion trap MS method in negative ion mode (Figure 9.11) for quantitating in urine 3-glucuronides of androsterone (An-3G), 11-ketoandrosterone (11-ketoAn-3G), 11beta-hydroxyandrosterone (11beta-OHAn-3G), dehydroepiandrosterone (DHEA-3G) and 17-glucuronides of testosterone (T-17G), epitestosterone (Epi-17G), and dihydrotestosterone (DHT-17G)) with LODs around 5-10 ng ml −1 [118].…”
Section: Dopingmentioning
confidence: 99%
“…Alternatively, an alkaline buffer can be used to induce ionization of weakly acidic free estrogens (p K a ≈ 10.4) for their resolution by CE without involatile detergent additives . Recently, Cho et al demonstrated the analysis of urinary androgen glucuronides by CE–ESI-MS/MS; however, the method required a dynamically coated capillary under reverse polarity that suffers from poor stability due to anodic corrosion of the stainless steel needle . In this report, we introduce for the first time a CE–MS strategy for comprehensive profiling of free estrogens together with their intact glucuronide and sulfate conjugates using an unmodified capillary under normal polarity (Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%